1992
DOI: 10.1029/92tc00241
|View full text |Cite
|
Sign up to set email alerts
|

Upper Jurassic‐Lower Cretaceous basinal strata along the Cordilleran Margin: Implications for the accretionary history of the Alexander‐Wrangellia‐Peninsular Terrane

Abstract: Abstract. Upper Jurassic and Lower

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 112 publications
5
152
0
Order By: Relevance
“…Late Jurassic and Early Cretaceous GravinaNutzotin deposits along the west flank of the Coast Mountains north of latitude 55° and in the TyaughtonMethow basin in their east side south of latitude 52° were thought to have accumulated in post-accretionary, backarc and/or dextral pull-apart basins (Figs. 1, 2, 3;Gehrels and Saleeby 1987;McClelland et al 1992;van der Heyden 1992). However, these models did not take into account the fact that the Jurassic-Cretaceous TyaughtonMethow basin in the southeastern Coast Mountains is floored by remnants of oceanic lithosphere, some of which, in the Bridge River terrane, are as young as latest Middle Jurassic (164 Ma) and possibly even younger.…”
Section: Discussionmentioning
confidence: 99%
“…Late Jurassic and Early Cretaceous GravinaNutzotin deposits along the west flank of the Coast Mountains north of latitude 55° and in the TyaughtonMethow basin in their east side south of latitude 52° were thought to have accumulated in post-accretionary, backarc and/or dextral pull-apart basins (Figs. 1, 2, 3;Gehrels and Saleeby 1987;McClelland et al 1992;van der Heyden 1992). However, these models did not take into account the fact that the Jurassic-Cretaceous TyaughtonMethow basin in the southeastern Coast Mountains is floored by remnants of oceanic lithosphere, some of which, in the Bridge River terrane, are as young as latest Middle Jurassic (164 Ma) and possibly even younger.…”
Section: Discussionmentioning
confidence: 99%
“…This composite terrane may have been accreted to the western margin of North America during mid-Cretaceous time, resulting in the widespread metamorphic and magmatic events of this age observed throughout coastal British Columbia and southeast Alaska (Monger et al, 1982;Crawford et al, 1987). McClelland and Gehrels (1990), McClelland et al (1992), and van der Heyden (1992) suggested that mid-Cretaceous colli- on November 29, 2014 lithosphere.gsapubs.org Downloaded from www.gsapubs.org | Volume 6 | Number 3 | LITHOSPHERE sional accretion was preceded by initial juxtaposition during mid-Jurassic time, followed by extension to form the Late Jurassic-Early Cretaceous Gravina basin (Fig. 1).…”
Section: U-pb and Hf Isotope Analysis Of Detrital Zircons From The Bamentioning
confidence: 99%
“…At that time, the Coast Belt formed as a tectonic welt resulting from the widespread plutonism, metamorphism and crustal shortening. However, other models argue that the superterranes were together by mid-Jurassic and the collisional orogen originated from intra-arc rifting and subsequent shortening (VAN DER HEYDEN, 1992;MCLELLAND et al, 1992). A partial resolution in the apparent conflict between these types of models has also been proposed (MONGER et al, 1994), involving left-lateral displacements before the mid-Cretaceous.…”
Section: Tectonic Settingmentioning
confidence: 99%